CURRENT STATUS OF THE POLE-AND-LINE FISHERY IN EASTERN PART OF INDONESIA - Agustinus Anung Widodo; Wudianto Wudianto; Fayakun Satria (Research Center for Fisheries, 2016)
The promotion of pole-and-line fishery for a selective gear operating in the Indonesian tuna management area is considered as the proper policy in response to the increasing market demand with tuna eco-labeled. Appropriate information in addressing the current status of the pole-and-line fishery in Indonesia is an important step in order to support the promotion. Data used to describe the fishery were obtained through scientific port sampling program in collaboration between RCFMC and WCPFC in 2010 to 2014 and also scientific observer onboard program collaboration RCFMC and CRAC Co. Ltd. in 2013. The results show that presently the number of pole and line fleets was decreased significantly and remain about 232 fleetsin Sorong, Bitung and Kendari and Larantuka. The national annual total catch of pole-and line during 1980 – 2013 was recorded between 24,000 and 160,000 tons per year (average 98,117 tons per year). This value is estimated to contribute about 20% of Indonesia annual total catch of tuna in FMAs713-717. The pole-andline catch rates based at Bitung, Kendari and Sorong were fluctuated in each year with the range respective between 8.79 and 17.93 tons/trip/vessel, 4.78 and 5.36 ton/trip/vessel and about 7,99 ton ton/trip/vessel. Pole-and-line fishery operated in Indonesian FMAs 713-717 is considered as selective fishery, with > 80 % catches of skipjack in matured stage. The tuna-live bait fish ratio in Indonesian pole-and-line was 4.41 :1, then an improvement of live bait ratio as well as its management is required.